2022
DOI: 10.3389/fenrg.2022.864645
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Aeroelastic Actuator Line for Wind Turbine Modelling in Complex Flows

Abstract: The actuator line method is a widely used technique to model wind turbines in computational fluid dynamics, as it significantly reduces the required computational expense in comparison to simulations using geometrically resolved blades. Actuator line coupled to an aeroelastic solver enables not only the study of detailed wake dynamics but also aeroelastic loads, flexible blade deformation and how this interacts with the flow. Validating aeroelastic actuator line predictions of blade loading, deflection and tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Overall, agreement in mean power to ≤ 7.2% and mean thrust to ≤ 6.4% between two different research group frameworks is significantly closer than in large benchmark studies [13], particularly when comparing across a range of non-neutral ABL inflows. The percentage differences are similar to that achieved using EllipSys3D and identical sheared inflow when comparing AL to a fully resolved rotor [38].…”
Section: A) B)supporting
confidence: 73%
See 1 more Smart Citation
“…Overall, agreement in mean power to ≤ 7.2% and mean thrust to ≤ 6.4% between two different research group frameworks is significantly closer than in large benchmark studies [13], particularly when comparing across a range of non-neutral ABL inflows. The percentage differences are similar to that achieved using EllipSys3D and identical sheared inflow when comparing AL to a fully resolved rotor [38].…”
Section: A) B)supporting
confidence: 73%
“…Therefore, Wake Conference 2023 Journal of Physics: Conference Series 2505 (2023) 012009 differences in normalised wake flow can be primarily attributed to the grid resolution. Other grid studies in EllipSys3D using laminar [11] or uniform turbulent inflow [38] have shown convergence of C T to within 1% for a stiff AD at R/(dxdydz) 1/3 ≥ 8, or for a flexible AL at R/(dxdydz) 1/3 ≥ 16 (both using uniform grids). The grid study results here, for a CNBL inflow, give a difference in mean C T between R/(dxdydz) 1/3 = 8 and 16 of only 0.2%, and so is consistent with previous findings in EllipSys3D.…”
Section: Single Turbine Wakesmentioning
confidence: 98%
“…Wind turbines are modelled using the actuator line (AL) method [17], which is fully coupled to the aeroelastic BEM-based tool Flex5 [18]. EllipSys3D extracts the velocity components at the actuator positions and passes them to Flex5, which calculates the blade loads and deflections using tabulated aerofoil data and the vortex-based smearing correction [19] [20] which is implemented in the blade load computation [21]. The loads and deformed blade positions are passed back to EllipSys3D, and used to update the actuator positions and the magnitude of the applied body forces, which are smeared on to the computational grid using a Gaussian kernel.…”
Section: Wind Turbine Modellingmentioning
confidence: 99%
“…The entire domain is discretised using 288 x 128 x 128 mesh points, resulting in a discretisation of 8 cells per radius inside the refined region. This is a relatively low resolution for an actuator line simulation, but judged to be acceptable due to the computational constraints and the fact that the vortex-based smearing correction implemented into the coupled AL reduces the difference in mean thrust coefficient between 8 and 64 cells per radius to 3% in a turbulent simulation [21]. Furthermore, the main objective here is to have the same relative thrust force for different flow scenarios, and not that the actual C T is converged through grid resolution.…”
Section: Computational Domainmentioning
confidence: 99%
“…More recently, OpenFAST was also coupled to Nalu-Wind and PALM [4,5] to study the NREL-5 MW reference wind turbine. Hodgson et al also performed validation of flexible actuator methods against high fidelity blade-resolved simulations, highlighting the ability of the ALM to accurately capture aeroelastic effect on rotors up to 5 MW [6,7,8]. Della Posta et al also considered a two-way coupling between a structural solver and an ALM, including the tower, for unsteady aerodynamics of the NREL-5 MW rotor [9,10].…”
Section: Introductionmentioning
confidence: 99%